UNDERSTANDING HOW A BLEND OF SCAFFOLDING INSTRUCTIONS FACILITATE CHINESE LANGUAGE TEACHING - Tam, Angela (PEOPLE: International Journal of Social Sciences, 2017)
Much attention has focused on linguistic scaffolding in language learning, little is known how a blend of scaffoldinginstructions facilitate Chinese language teaching in Putonghua-Medium-of-instruction (PMI) classroom encompassing linguistic, cognitive, cultural, affective and social (LCCAS) aspects. Lessons of a secondary school teacher who attended a professional development workshop were observed. The findings indicate that the use of different scaffolding instructions tailored to the needs of studentsenable students to achieve Chinese Language and Putonghua learning through scaffolding in various aspects: (1) provision of linguistic scaffolding to students to adapt Putonghua instruction, (2) foster cognitive development by association of students’ academic background knowledge with meaningful instruction, (3) connect the cultural and historical understandings of learners with the texts, (4) develop positive attitudes towards a switch of PMI from mother tongue to arouse the learning motivation of learners, and (5) stimulation of peer interaction and cooperation. Quantitative studies and cross-case qualitative studies examining this new conceptual framework on teachers’ scaffolding are suggested for future studies.